2.5 D woven carbon fiber preform reinforced Zr-based composite material and preparation method thereof

Through the deposition thermal dissolving carbon interface and introducing resin/ceramic particles in the pre-pre-made pre-pre-made body of the 2.5D machine, combined with the reaction melting osmotic method to embed the ZR-SI alloy powder, solve the length of long and low density in the existing technology The problem of 2.5D woven carbon fiber prefabricated in the 2.5D woven carbon fiber prefabricated material reinforcement of ZR base composite materials with high density and low pore rate.

CN119372567APending Publication Date: 2025-01-28NORTHWESTERN POLYTECHNICAL UNIV +1

Patent Information

Application Number
CN202411728865.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-28

Smart Images

  • Figure CN119372567A_ABST
    Figure CN119372567A_ABST
Patent Text Reader

Abstract

The invention discloses a 2.5 D woven carbon fiber preform reinforced Zr-based composite material and a preparation method thereof, and belongs to the technical field of ceramic-based composite material preparation. The preparation method comprises the following steps: depositing a pyrolytic carbon interface phase in a 2.5 D woven carbon fiber preform through a chemical vapor infiltration method to prepare a low-density C / PyC composite material; placing the low-density C / PyC composite material in a resin / ceramic solution for primary impregnation and ultrasonic treatment to prepare a C / (PyC-R) composite material; the C / (PyC-R) composite material and a resin / ceramic solution are poured into a mold, demolding is conducted after drying, then carbonization is conducted, and a C / (PyC-RC) composite material is obtained, cleaned and dried; a reaction infiltration method is adopted, Zr-Si alloy powder is embedded around the cleaned and dried C / (PyC-RC) composite material, high-temperature heat treatment is carried out in vacuum, and the 2.5 D woven carbon fiber preform reinforced Zr-based composite material is prepared. The preparation method can solve the technical problems of low densification degree and long preparation period in the process of preparing the three-dimensional composite material with large-size pores in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic-based composite material preparation, and specifically relates to a 2.5D woven carbon fiber preform reinforced Zr-based composite material and a preparation method thereof. Background Art

[0002] The development of high-speed aircraft has put forward higher requirements for thermal protection materials. Ultra-high temperature ceramics mainly refer to carbides, borides and nitrides of refractory metals of IVB and VB groups with melting points above 3000°C, such as ZrC, HfC, TaC, ZrB2 and HfB2, etc. They have a series of excellent properties such as high melting point, high hardness and corrosion resistance. The refractory metal oxides formed after ablation also have high melting points and excellent high-temperature stability, and are considered to be ideal thermal protection system materials. However, ultra-high temperature ceramics have high density and high brittleness. Ceramic-based composites made of high-strength and high-toughness carbon fibers as reinforcements have a series of advantages such as low density, high temperature resistance, high strength and toughness, and anti-oxidation and ablation. Therefore, ceramic-based composites have become an important candidate material in aircraft thermal protection systems.

[0003] At present, for ceramic matrix composite samples or components, the common carbon fiber preform structures are mainly divided into needle punched preforms, three-dimensional braided preforms and three-dimensional woven preforms. The needle punched preform is a quasi-three-dimensional mesh structure reinforcement with certain strength in both plane and interlayer by alternately stacking non-weft cloth and mesh fiber. Due to the special structure of needle punched non-weft cloth / mesh composite fabric, it has the characteristics of small pore size (tens to hundreds of microns) and uniform distribution, easy to compact molding, but its interlayer bonding is weak. Three-dimensional braided preforms and three-dimensional woven preforms have the advantages of good interlayer connection performance, high strength and overall net shape, and are important skeleton structures for ideal candidate materials for hot end components of high-speed aircraft. The three-dimensional braided preform uses braiding technology to interlace and interweave fiber bundles in three-dimensional space to form an integral structure. The interlacing of fiber bundles during the weaving process can reduce the formation of pores, so the internal pore structure of the three-dimensional braided composite material is relatively uniform. The three-dimensional woven preform is made by weaving fiber yarns in three directions: length, width and thickness. The basic elements of the fabric are composed of warp and weft yarns. Compared with the three-dimensional woven structure, it has significant advantages such as rapid prototyping and low production cost. However, the internal pore structure of the woven preform may become uneven due to the interlayer sliding, squeezing and dislocation of the fiber bundles. This unevenness may cause stress concentration and damage, thereby affecting the performance of the composite material. In addition, due to the mutual pressure of the yarns themselves during the weaving process of the woven preform, the spatial path of the yarns, and the inversion symmetry of the adjacent layers of warp yarns, large-sized pores (>2mm) exist in the composite material, which is difficult to achieve densification. Therefore, compared with the needle-punched and woven structures, the pore structure of the woven structure is more complex and more difficult to achieve densification.

[0004] The 2.5D woven structure is a special three-dimensional woven structure, which is formed by interweaving two yarn systems in the warp, weft and thickness directions to form a three-dimensional fabric. Due to the distribution of yarns in the thickness direction, the 2.5D woven structure has good near-net forming ability and excellent interlayer mechanical properties, and can resist the delamination phenomenon caused by complex external load conditions. Therefore, the use of 2.5D woven preforms as reinforcements for ceramic-based composites is conducive to improving the mechanical properties of composites.

[0005] Chemical vapor infiltration, precursor impregnation pyrolysis and reactive melt infiltration are the most commonly used methods for preparing ceramic matrix composites. Limited by the complex woven structure, large-scale and uneven pore distribution, there are few studies on the use of 2.5D woven carbon fiber preforms as reinforcements to prepare Zr-based composites.

[0006] The Chinese patent with patent publication number CN111099911B discloses a carbon fiber reinforced carbon-silicon carbide-zirconium carbide composite material and its preparation method. This method uses a carbon fiber needle-punched preform as a reinforcement, prepares a solution with silicon powder, zirconium powder, graphite powder and phenolic resin as raw materials, and then uses a mixed resin solution to impregnate the needle-punched carbon fiber preform, and prepares the composite material through multiple impregnation-curing-carbonization cycles. However, the pores of the needle-punched preform used in this method are relatively uniform and easy to fill densely, and the preparation process cycle is long.

[0007] Han et al. (Han N, Duan Y, Zhang Z, et al. Fracture toughness and progressive damage mechanisms of 2.5D woven SiC f / SiC composites:[J].Journal of Reinforced Plastics and Composites, 2024, 43(7-8):398-410.) 2.5D woven SiC was prepared by precursor impregnation pyrolysis method. f / SiC composite materials require repeated "impregnation-cracking" process for more than 12 cycles during preparation, resulting in a long preparation cycle. In addition, during the PCS cracking process, the escape of small molecules will form more pore defects in the matrix. Finally, the composite material has a high open porosity and large pores are difficult to fill densely.

[0008] Therefore, how to reduce the influence of large-sized pores on the melt infiltration process and improve the efficiency of densification is the key to preparing 2.5D woven carbon fiber preform woven reinforced ceramic matrix composites. The existing preparation methods of 2.5D woven composites cannot have the advantages of short cycle and high densification degree. Summary of the invention

[0009] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a 2.5D woven carbon fiber preform reinforced Zr-based composite material and a preparation method thereof, which can not only reduce the adverse effects of large-size pores on the melt infiltration process and significantly improve the densification efficiency, but also effectively shorten the overall preparation cycle, so as to solve the technical problems of low densification degree and long preparation cycle in the process of preparing three-dimensional composite materials with large-size pores in the existing process.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material, comprising the following steps: S1: Low-density C / PyC composites were prepared by chemical vapor infiltration by depositing pyrolytic carbon interfacial phase inside 2.5D woven carbon fiber preforms; S2: The low-density C / PyC composite material is placed in a resin / ceramic solution for one-time impregnation and ultrasonication to obtain a C / (PyC-R) composite material; S3: pouring the C / (PyC-R) composite material and the resin / ceramic solution into a mold, drying and demolding, and then carbonizing to obtain a C / (PyC-RC) composite material, which is then cleaned and dried; S4: The Zr-Si alloy powder was embedded around the cleaned and dried C / (PyC-RC) composite material by reactive infiltration method, and high-temperature heat treatment was performed under vacuum to obtain a 2.5D woven carbon fiber preform reinforced Zr-based composite material.

[0011] In one embodiment, the 2.5D woven carbon fiber preform is a 2.5D layer-layer angle interlocking woven preform with a shallow cross-connected structure, the number of warp yarns is 2, the number of weft yarns is 4, and the density is 0.7-0.9 g / cm 3 , the fiber volume fraction is 40~60%.

[0012] In one embodiment, during the deposition of the pyrolytic carbon interface phase, the carbon source precursor is methane and the protective gas is argon; the flow ratio of methane to argon is (20-30): 1, the deposition temperature is 900-1200°C, and the deposition time is 100-300h.

[0013] In one embodiment, the density of the low-density C / PyC composite material is 1.3-1.6 g / cm 3 .

[0014] In one embodiment, the resin / ceramic solution is prepared as follows: Firstly, the resin is dissolved in an ethanol solution, and then ceramic particles are added and stirred evenly to obtain a resin / ceramic solution; Wherein, the resin is phenolic resin or furan resin, and the mass concentration of the resin is 50-80%; The ceramic particles are ZrB2 particles, the particle size of the ZrB2 particles is 1-3 μm, and the added amount of the ceramic particles is 30-50% of the mass of the resin.

[0015] In one embodiment, the ultrasonication time is 10 to 20 minutes.

[0016] In one embodiment, the drying temperature is 70-80° C., and the drying time is 20-30 hours.

[0017] In one embodiment, the carbonization process parameters are: in an argon atmosphere, heating to 300° C. at 3-5° C. / min, keeping warm for 1-2 hours, then heating to 800-1000° C. at 3-7° C. / min, keeping warm for 2-3 hours.

[0018] In one embodiment, the particle size of the Zr-Si alloy powder is 2-50 μm, and the purity is 99.90-99.95%; the heating rate of the high temperature heat treatment is 5-10° C. / min, the temperature is raised to 1600-1900° C., and the holding time is 1-3 hours.

[0019] The present invention also provides a 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared according to any one of the methods for preparing the 2.5D woven carbon fiber preform reinforced Zr-based composite material.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material. First, pyrolytic carbon is uniformly deposited on the surface of carbon fiber in the form of ring growth. Then, resin carbon / ceramic particles are pre-introduced into large-sized pores of C / PyC composite material through resin / ceramic particle impregnation, drying and carbonization processes. The resin carbon / ceramic particles shrink the large-sized pores into small pores, which is beneficial to the subsequent infiltration and reaction of melt, so as to prepare a relatively dense 2.5D woven carbon fiber preform reinforced ceramic-based composite material. Placing the resin solution and the composite material into an oven for drying together can shorten the number of impregnation times and improve the efficiency of resin impregnation. The resin can be effectively filled into the composite material through only one "impregnation-drying-carbonization" step. The 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared by the one-time resin impregnation combined with the reaction melt infiltration method used in the above preparation method can effectively shorten the preparation cycle compared to the precursor impregnation pyrolysis method or other impregnation methods. Compared with the 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared by the traditional reaction melt infiltration method, the density is increased and the porosity is reduced.

[0021] Furthermore, adding ceramic particles to the resin solution can increase the ceramic phase content in the composite material, thereby improving the ablation performance of the composite material. In addition, using ethanol as the solvent for the resin / ceramic solution can effectively penetrate into the pores of the C / PyC composite material through ultrasonic impregnation, thereby avoiding the agglomeration of ceramic particles.

[0022] Furthermore, the resin shrinks and cracks during the carbonization process, occupying the middle position of the large-sized pores, which can reduce the loss of the melt during the infiltration process. At the same time, the higher specific surface area can accelerate the reaction between the melt and the carbon matrix, which is beneficial to the formation of the ceramic phase.

[0023] The present invention also provides a 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared by the above preparation method, the density of which is 2.50-3.10 g / cm 3 , with a porosity of 7-12%. Compared with the 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared by the traditional reaction infiltration method, the porosity is reduced by 70.6%. The ceramic matrix formed in situ by the Zr-Si melt fills the pores in the composite material, and the carbon matrix and the ceramic matrix are evenly distributed, which improves the thermal conductivity and ablation resistance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the internal pore structure of the C / PyC composite material obtained after depositing pyrolytic carbon in Example 1; Among them: Figure a-2mm; Figure b-1mm; Figure c-2mm; Figure d-500μm; Figure e-5mm; Figure f-500μm; Figure 2 This is a SEM image of the internal pore structure of the C / (PyC-RC) composite material obtained by introducing resin carbon in Example 1; Among them: Figure a-2mm; Figure b-500μm; Figure 3 The X-ray diffraction pattern of the 2.5D woven carbon fiber preform reinforced Zr-based composite material obtained in Example 1; Figure 4 This is a cross-sectional SEM image of the 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared in Example 1.

[0025] Among them: Figure a-2mm; Figure b-500μm; Figure 5 This is a flow chart of a method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material provided by one embodiment of the present invention. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0027] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0028] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0029] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0030] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0031] The invention provides a 2.5D woven carbon fiber preform reinforced Zr-based composite material and a preparation method thereof, belonging to the field of ceramic-based composite material preparation.

[0032] like Figure 5 As shown, the preparation method is as follows: chemical vapor infiltration is used to introduce an interface phase into a 2.5D woven carbon fiber preform, and then a resin / ceramic solution is prepared, which is immersed in the resin / ceramic solution for ultrasonic and impregnation, and a resin / ceramic intermediate is introduced, and then drying and carbonization are performed to obtain a low-density 2.5D woven carbon fiber preform reinforced carbon-based composite material, and then reactive dissolution is performed to obtain a 2.5D woven carbon fiber preform reinforced Zr-based composite material.

[0033] The above-mentioned preparation method first deposits a pyrolytic carbon interface phase inside a 2.5D woven carbon fiber preform by chemical vapor infiltration, and then introduces resin / ceramics into the matrix to fill part of the pores by impregnation, ultrasound, drying and carbonization; finally, a reactive infiltration process is used to react the Zr-Si alloy with the carbon matrix to generate a Zr-based ceramic, and finally a 2.5D woven carbon fiber preform reinforced Zr-based composite material is obtained.

[0034] In the above preparation method, on the one hand, the "impregnation-drying-carbonization" process is used to fill the resin carbon into the large-size pores (>2mm) of the 2.5D woven structure; on the other hand, the reactive infiltration process is used, and the melt infiltrates into the residual pores at high temperature to react in situ to generate a ceramic phase, thereby preparing a relatively dense 2.5D woven carbon fiber preform reinforced Zr-based composite material.

[0035] The present invention provides a method for preparing a 2.5D woven carbon fiber preform reinforced ceramic matrix composite material, comprising the following steps: S1: Using chemical vapor infiltration, a pyrolytic carbon (PyC) interface layer is deposited inside the carbon fiber preform to obtain a low-density C / PyC composite material; S2: placing the low-density C / PyC composite material in a resin (R) / ceramic solution for one-time impregnation and ultrasonication to obtain a C / (PyC-R) composite material; S3: pouring the C / (PyC-R) composite material and the resin / ceramic solution into a mold, drying and demolding, and then carbonizing to obtain a C / (PyC-RC) composite material, which is then cleaned and dried; S4: The cleaned and dried C / (PyC-RC) composite material was placed in a graphite crucible by reactive infiltration, Zr-Si alloy powder was embedded around it, and high-temperature heat treatment was performed under vacuum to obtain a 2.5D woven carbon fiber preform reinforced ceramic matrix composite material.

[0036] Furthermore, in step S1, the carbon fiber preform is a 2.5D layer-layer angle interlocking woven preform with a shallow cross-connected structure, the number of warp yarns is 2, the number of weft yarns is 4, and the density is 0.7-0.9 g / cm 3 , the fiber volume fraction is 40~60%.

[0037] Furthermore, in step S1, the method for introducing the pyrolytic carbon interface layer is: introducing by chemical vapor infiltration, wherein the carbon source precursor is methane, the protective gas is argon, the flow ratio of methane to argon is (20-30): 1, the deposition temperature is 900-1200°C, and the deposition time is 100-300h.

[0038] The chemical vapor infiltration method prepared 1.3~1.6g / cm 3 Low density C / PyC composites.

[0039] Furthermore, in step S2, the resin / ceramic solution is prepared by first dissolving the resin in an ethanol solution, then adding ceramic particles and stirring evenly; The resin is any one of phenolic resin or furan resin, and the mass concentration of the resin is 50-80%; The ceramic particles are ZrB2 particles with a particle size of 1-3 μm, and the amount of ceramic particles added is 30-50% of the resin mass.

[0040] The stirring method is magnetic stirring; the stirring time is 20 to 60 minutes.

[0041] Furthermore, in step S2, the impregnation process is to first place the sample (low-density C / PyC composite material) into the prepared resin / ceramic solution, then place the beaker in an ultrasonicator for 10 to 20 minutes, and finally pour the prepared sample (C / (PyC-R) composite material) and the resin / ceramic solution into a silicone mold, so that the sample (C / (PyC-R) composite material) is always immersed in the resin / ceramic solution.

[0042] Specifically, in S3, after drying, the solid formed by the sample (C / (PyC-R) composite material) and the resin in the resin / ceramic solution is demolded and then carbonized.

[0043] Furthermore, in step S3, the drying temperature is 70-80°C, and the drying time is 20-30h. The carbonization process parameters are: in an argon atmosphere, the temperature is increased to 300°C at 3-5°C / min, kept at this temperature for 1-2h, and then increased to 800-1000°C at 3-7°C / min, and kept at this temperature for 2-3h.

[0044] Furthermore, in step S4, the particle size of the Zr-Si alloy powder is 2-50 μm, and the purity is 99.90-99.95%.

[0045] Furthermore, in step S4, the heating rate of the reaction infiltration process (high temperature heat treatment) is 5-10°C / min, the temperature is raised to 1600-1900°C, and the holding time is 1-3h.

[0046] Another aspect of the present invention also provides a 2.5D woven carbon fiber preform reinforced ceramic-based composite material obtained by the above-mentioned preparation method.

[0047] The 2.5D woven carbon fiber preform reinforced ceramic matrix composite material prepared by the above method has the advantages of short preparation time and high density. The above method introduces resin carbon into the large-sized pores of the 2.5D woven preform, and generates Zr-based ceramics in situ by means of a reactive infiltration method. The ceramic matrix formed in situ fills the remaining pores in the composite material, and the carbon matrix and the ceramic matrix are evenly distributed, which can improve the thermal conductivity and ablation resistance of the composite material.

[0048] An embodiment of the present invention provides a method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material, comprising the following steps: Step 1, preparation of low-density C / PyC: The pyrolytic carbon interface layer was deposited on the 2.5D woven carbon fiber preform by chemical vapor infiltration process to obtain a density of 1.3~1.6g / cm 3 Low-density C / PyC composites; Step 2, preparation of resin / ceramic solution: Dissolve phenolic resin or furan resin in ethanol to obtain a resin solution, and add ceramic particles to the resin solution. The mass concentration of the resin is 50-80%, and the amount of ceramic particles (particle size 1-3 μm) added is 30-50% of the resin mass. The suspension is magnetically stirred for 20-60 minutes to obtain a mixed solution. Step 3: Impregnation of resin / ceramic solution: The low-density C / PyC composite material obtained in step 1 is immersed in the resin / ceramic solution obtained in step 2, so that the block of low-density C / PyC composite material is completely immersed, and then placed in an ultrasonic instrument for 10 to 20 minutes, and finally the C / (PyC-R) composite material and the resin / ceramic solution are poured into a silicone mold, so that the sample is always immersed in the solution; Step 4: Drying and carbonization of the solution: Place the silicone mold containing the sample C / (PyC-R) composite material and resin / ceramic solution obtained in step 3 into an oven at a temperature of 70-80°C for 20-30 hours; after drying, demould the solid formed by the C / (PyC-R) composite material and the resin. Carbonize the demoulded C / (PyC-R) composite material at high temperature to crack the resin in the C / (PyC-R) composite material into carbon, and obtain a C / (PyC-RC) composite material; Step 5: Reaction Infiltration: The C / (PyC-RC) composite material obtained in step 4 is washed and dried and then placed in a graphite crucible, and Zr-Si alloy powder (particle size of 2-50 μm, purity of 99.90-99.95%) is placed around it to wrap it with the alloy powder and seal the crucible. The crucible is placed in a high-temperature furnace for heat treatment to obtain a 2.5D woven carbon fiber preform reinforced Zr-based composite material; Preferably, the carbon fiber preform used in step 1 is a 2.5D layer-layer angle interlocking woven preform with a shallow cross-connected structure, with 2 warp yarns, 4 weft yarns, and a density of 0.7-0.9 g / cm 3 , the fiber volume fraction is 40~60%.

[0049] Preferably, the chemical vapor infiltration process used in step 1 to prepare the pyrolytic carbon interface layer is as follows: the carbon source precursor is methane, the protective gas is argon, the flow ratio of methane to argon is (20-30): 1, the deposition temperature is 900-1200°C, and the deposition time is 100-300h.

[0050] Preferably, the carbonization process used in step 4 is: in an argon atmosphere, heating to 300° C. at 3-5° C. / min, keeping warm for 1-2 hours, then heating to 800-1000° C. at 3-7° C. / min, keeping warm for 2-3 hours.

[0051] Preferably, the heat treatment process in the reaction infiltration process adopted in step 5 is: in a vacuum atmosphere, the heating rate is 5-10°C / min, the temperature is raised to 1800°C, the heat preservation time is 2h, and then the power is turned off and the temperature is cooled.

[0052] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0053] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercial products, and their specifications are conventional specifications in the art.

[0054] Example 1 A method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material comprises the following steps: Step 1, preparation of low-density C / PyC: The pyrolytic carbon interface layer was deposited on the 2.5D woven carbon fiber preform by chemical vapor infiltration process. The carbon fiber preform was a 2.5D layer-layer angle interlocking woven preform with a shallow cross-linked structure, 2 warp yarns, 4 weft yarns, and a density of 0.85 g / cm 3 , the fiber volume fraction is 46%. The carbon source precursor is methane, the protective gas is argon, the argon flow rate is 3L / min, the natural gas flow rate is 70L / min, the deposition temperature is 1100℃, and the deposition time is 150h. The density is 1.3g / cm 3 Low density C / PyC; Step 2, preparation of solution: The phenolic resin was dissolved in ethanol, and the mass concentration of the resin was 60%; the suspension was magnetically stirred for 50 minutes to obtain a mixed solution; Step 3: Impregnation of solution: The low-density C / PyC composite material obtained in step 1 is immersed in the solution obtained in step 2, so that the block is completely immersed, and then placed in an ultrasonic instrument for 15 minutes, and finally the sample and the solution are poured into a silicone mold, so that the sample is always immersed in the solution; Step 4: Drying and carbonization of the solution: Place the silicone mold containing the sample and solution obtained in step 3 into an oven at 70°C for 24 hours; after drying, demold the solid formed by the composite material and the resin. Place the demolded material in a heat treatment furnace, and heat it to 300°C at 3°C / min under an argon atmosphere, keep it warm for 2 hours, then heat it to 900°C at 5°C / min, and keep it warm for 2 hours. The resin in the composite material is cracked into carbon to obtain C / (PyC-RC); Step 5: Reaction Infiltration: The composite material obtained in step 4 was cleaned and dried, and then placed in a graphite crucible. Zr-Si alloy powder (particle size 50 μm, purity 99.95%) was placed around it to wrap it with the alloy powder and seal the crucible. The crucible was placed in a high-temperature furnace, and the temperature was raised to 1800°C at a rate of 10°C / min under vacuum atmosphere. After the temperature was kept for 2 hours, the power was turned off and the temperature was cooled. After heat treatment, the density was 2.74 g / cm 3 , 2.5D woven carbon fiber preform reinforced Zr-based composite material with a porosity of 7.01%.

[0055] Example 2 A method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material comprises the following steps: Step 1, preparation of low-density C / PyC: The pyrolytic carbon interface layer was deposited on the 2.5D woven carbon fiber preform by chemical vapor infiltration process. The carbon fiber preform was a 2.5D layer-layer angle interlocking woven preform with a shallow cross-linked structure, 2 warp yarns, 4 weft yarns, and a density of 0.85 g / cm 3 , the fiber volume fraction is 46%. The carbon source precursor is methane, the protective gas is argon, the argon flow rate is 3L / min, the natural gas flow rate is 70L / min, the deposition temperature is 1100℃, and the deposition time is 150h. The density is 1.3g / cm 3 Low density C / PyC; Step 2, preparation of resin / ceramic solution: The phenolic resin was dissolved in ethanol to obtain a resin solution, the mass concentration of the resin was 60%, ZrB2 ceramic particles were added to the resin solution, the amount of ZrB2 ceramic particles (particle size 3 μm) added was 33% of the resin mass, the suspension was magnetically stirred for 50 minutes, and a mixed solution was obtained; Step 3: Impregnation of solution: The low-density C / PyC obtained in step 1 was immersed in the solution obtained in step 2, so that the block was completely immersed, and then placed in an ultrasonicator for 15 minutes. Finally, the sample and the solution were poured into a silicone mold, so that the sample was always immersed in the solution; Step 4: Drying and carbonization of the solution: Place the silicone mold containing the sample and solution obtained in step 3 into an oven at 70°C for 24 hours; after drying, demould the solid formed by the composite material and the resin. Place the demoulded material in a heat treatment furnace, and heat it to 300°C at 3°C / min in an argon atmosphere, keep it warm for 2 hours, and then heat it to 900°C at 5°C / min, and keep it warm for 2 hours. The resin in the composite material is cracked into carbon to obtain C / (PyC-RC); Step 5: Reaction Infiltration: The composite material obtained in step 4 was cleaned and dried, and then placed in a graphite crucible. Zr-Si alloy powder (particle size 50 μm, purity 99.95%) was placed around it to wrap it with the alloy powder and seal the crucible. The crucible was placed in a high-temperature furnace, and the temperature was raised to 1800°C at a rate of 8°C / min under vacuum atmosphere. After the temperature was kept for 2 hours, the power was turned off and the temperature was cooled. After heat treatment, the density was 3.02 g / cm 3 , 2.5D woven carbon fiber preform reinforced Zr-based composite material with a porosity of 11.11%.

[0056] Example 3 A method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material comprises the following steps: Step 1, preparation of low-density C / PyC: The pyrolytic carbon interface layer was deposited on the 2.5D woven carbon fiber preform by chemical vapor infiltration. The carbon fiber preform was a 2.5D layer-layer angle interlocking woven preform with a shallow cross-linked structure, 2 warp yarns, 4 weft yarns, and a density of 0.7 g / cm 3 , the fiber volume fraction is 40%. The carbon source precursor is methane, the protective gas is argon, the argon flow rate is 3L / min, the natural gas flow rate is 60L / min, the deposition temperature is 900℃, and the deposition time is 200h. The density is 1.42g / cm 3 Low density C / PyC; Step 2, preparation of resin / ceramic solution: The phenolic resin was dissolved in ethanol to obtain a resin solution, the mass concentration of the resin was 50%, ZrB2 ceramic particles were added to the resin solution, the amount of ZrB2 ceramic particles (particle size 1 μm) added was 30% of the resin mass, the suspension was magnetically stirred for 20 minutes, and a mixed solution was obtained; Step 3: Impregnation of solution: The low-density C / PyC obtained in step 1 is immersed in the solution obtained in step 2, so that the block is completely immersed, and then placed in an ultrasonic instrument for 10 minutes. Finally, the sample and the solution are poured into a silicone mold, so that the sample is always immersed in the solution; Step 4: Drying and carbonization of the solution: Place the silicone mold containing the sample and solution obtained in step 3 into an oven at a temperature of 75°C for 20 hours; after drying, demould the solid formed by the composite material and the resin. Place the demoulded material in a heat treatment furnace, and heat it to 300°C at 3°C / min in an argon atmosphere, keep it warm for 1 hour, and then heat it to 800°C at 3°C / min, and keep it warm for 2 hours. The resin in the composite material is cracked into carbon to obtain C / (PyC-RC); Step 5: Reaction Infiltration: The composite material obtained in step 4 was cleaned and dried, and then placed in a graphite crucible. Zr-Si alloy powder (particle size 2 μm, purity 99.90%) was placed around it to wrap it with the alloy powder and seal the crucible. The crucible was placed in a high-temperature furnace, and the temperature was raised to 1800°C at a rate of 5°C / min under vacuum atmosphere. After the temperature was kept for 2 hours, the power was turned off and the temperature was cooled. After heat treatment, the density was 3.03 g / cm 3 , 2.5D woven carbon fiber preform reinforced Zr-based composite material with a porosity of 12.00%.

[0057] Example 4 A method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material comprises the following steps: Step 1, preparation of low-density C / PyC: The pyrolytic carbon interface layer was deposited on the 2.5D woven carbon fiber preform by chemical vapor infiltration. The carbon fiber preform was a 2.5D layer-layer angle interlocking woven preform with a shallow cross-linked structure, 2 warp yarns, 4 weft yarns, and a density of 0.9 g / cm 3 , the fiber volume fraction is 60%. The carbon source precursor is methane, the protective gas is argon, the argon flow rate is 3L / min, the natural gas flow rate is 90L / min, the deposition temperature is 1200℃, and the deposition time is 300h. The density is 1.6g / cm 3 Low density C / PyC; Step 2, preparation of resin / ceramic solution: The phenolic resin was dissolved in ethanol to obtain a resin solution, the mass concentration of the resin was 80%, ZrB2 ceramic particles were added to the resin solution, the amount of ZrB2 ceramic particles (particle size 3 μm) added was 50% of the mass of the resin, and the suspension was magnetically stirred for 60 minutes to obtain a mixed solution; Step 3: Impregnation of solution: The low-density C / PyC obtained in step 1 is immersed in the solution obtained in step 2, so that the block is completely immersed, and then placed in an ultrasonic instrument for 20 minutes. Finally, the sample and the solution are poured into a silicone mold, so that the sample is always immersed in the solution; Step 4: Drying and carbonization of the solution: Place the silicone mold containing the sample and solution obtained in step 3 into an oven at 80°C for 30 hours; after drying, demould the solid formed by the composite material and the resin. Place the demoulded material in a heat treatment furnace, and heat it to 300°C at 5°C / min in an argon atmosphere, keep it warm for 2 hours, and then heat it to 1000°C at 7°C / min, and keep it warm for 3 hours. The resin in the composite material is cracked into carbon to obtain C / (PyC-RC); Step 5: Reaction Infiltration: The composite material obtained in step 4 was cleaned and dried, and then placed in a graphite crucible. Zr-Si alloy powder (particle size 2 μm, purity 99.90%) was placed around it to wrap it with the alloy powder and seal the crucible. The crucible was placed in a high-temperature furnace, and the temperature was raised to 1800°C at a rate of 5°C / min under vacuum atmosphere. After the temperature was kept for 2 hours, the power was turned off and the temperature was cooled. After heat treatment, the density was 2.94 g / cm 3 , 2.5D woven carbon fiber preform reinforced Zr-based composite material with a porosity of 12.39%.

[0058] Comparative Example 1 A method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material comprises the following steps: Step 1, preparation of low-density C / PyC: The pyrolytic carbon interface layer was deposited on the 2.5D woven carbon fiber preform by chemical vapor infiltration process. The carbon fiber preform was a 2.5D layer-layer angle interlocking woven preform with a shallow cross-linked structure, 2 warp yarns, 4 weft yarns, and a density of 0.85 g / cm 3 , the fiber volume fraction is 46%. The carbon source precursor is methane, the protective gas is argon, the argon flow rate is 3L / min, the natural gas flow rate is 70L / min, the deposition temperature is 1100℃, and the deposition time is 150h. The density is 1.34g / cm 3 Low density C / PyC; Step 2: Reaction Infiltration: The composite material obtained in step 4 was washed and dried, and then placed in a graphite crucible. Zr-Si alloy powder (particle size of 2-50 μm, purity of 99.90-99.95%) was placed around it to wrap it with the alloy powder and seal the crucible. The crucible was placed in a high-temperature furnace, and the temperature was raised to 1800°C at a rate of 10°C / min under vacuum atmosphere. After the heat treatment was turned off for 2 hours, the density was 2.45 g / cm 3 , 2.5D woven carbon fiber preform reinforced Zr-based composite material with a porosity of 23.85%.

[0059] Compared with Comparative Example 1, the density of the 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared in Example 1 was increased by 11.8%, and the porosity was reduced by 70.6%. The density of the 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared in Example 2 was increased by 23.3%, and the porosity was reduced by 53.4%.

[0060] Figure 1 The middle figures (a-f) are SEM images of the internal pore structure of the C / PyC composite material obtained after depositing pyrolytic carbon in Example 1. Figure 1 It can be seen that the warp and weft yarns are in the shape of a sine curve and a straight line respectively, the weft yarn cross section is in the shape of a double convex lens, and the warp yarn cross section is in the shape of a capsule. The thickness of PyC is about 6μm, tightly surrounding the carbon fiber. The warp and weft yarns form "oblong" large-sized pores (length > 2mm), and these large-sized pores are distributed on the lower side of the junction of the warp and weft yarns.

[0061] Figure 2 The middle figure (a-b) is the SEM image of the internal pore structure of the C / (PyC-RC) composite material obtained by introducing resin carbon in Example 1. Figure 2 It can be seen that the introduced resin carbon is distributed in the large-sized pores of the matrix, and defects such as cracks appear in the resin carbon due to the escape of pyrolysis gas and volume shrinkage during high-temperature cracking.

[0062] Figure 3 The X-ray diffraction pattern of the 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared in Example 1 is shown in FIG. Figure 3 It can be seen that the XRD peaks are C peak, ZrC peak, SiC peak and Zr x Si y peak, proving that 2.5D woven carbon fiber preform reinforced Zr-based composites were successfully produced.

[0063] Figure 4 The middle figure (a-b) is a cross-sectional SEM image of the 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared in Example 1. Figure 4 It can be seen that the pores in the composite material are filled with ceramic and residual carbon, and the matrix density is improved.

[0064] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material, characterized in that: The following steps are involved: S1: A low-density C / PyC composite material is prepared by depositing a pyrolytic carbon interface phase inside a 2.5D woven carbon fiber preform by chemical vapor infiltration; the density of the 2.5D woven carbon fiber preform is 0.7-0.9 g / cm 3 ; S2: The low-density C / PyC composite material is placed in a resin / ceramic solution for one-time impregnation and ultrasonication to obtain a C / (PyC-R) composite material; S3: pouring the C / (PyC-R) composite material and the resin / ceramic solution into a mold, drying and demolding, and then carbonizing to obtain a C / (PyC-RC) composite material, which is then cleaned and dried; S4: The Zr-Si alloy powder was embedded around the cleaned and dried C / (PyC-RC) composite material by reactive infiltration method, and high-temperature heat treatment was performed under vacuum to obtain a 2.5D woven carbon fiber preform reinforced Zr-based composite material.

2. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: The 2.5D woven carbon fiber preform is a 2.5D layer-layer angle interlocking woven preform with a shallow cross-connected structure, the number of warp yarns is 2, the number of weft yarns is 4, and the fiber volume fraction is 40-60%.

3. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: In the process of depositing the pyrolytic carbon interface phase, the carbon source precursor is methane and the protective gas is argon; the flow ratio of methane to argon is (20-30):1, the deposition temperature is 900-1200°C, and the deposition time is 100-300h.

4. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: The density of the low-density C / PyC composite material is 1.3-1.6 g / cm 3 .

5. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: The preparation process of the resin / ceramic solution is as follows: Firstly, the resin is dissolved in an ethanol solution, and then ceramic particles are added and stirred evenly to obtain a resin / ceramic solution; Wherein, the resin is phenolic resin or furan resin, and the mass concentration of the resin is 50-80%; The ceramic particles are ZrB2 particles, the particle size of the ZrB2 particles is 1-3 μm, and the added amount of the ceramic particles is 30-50% of the mass of the resin.

6. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: The ultrasonic time is 10 to 20 minutes.

7. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: The drying temperature is 70-80° C., and the drying time is 20-30 hours.

8. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: The carbonization process parameters are: in an argon atmosphere, heating to 300° C. at 3-5° C. / min, keeping warm for 1-2 hours, then heating to 800-1000° C. at 3-7° C. / min, keeping warm for 2-3 hours.

9. The method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to claim 1, characterized in that: The particle size of the Zr-Si alloy powder is 2-50 μm, and the purity is 99.90-99.95%; the heating rate of the high-temperature heat treatment is 5-10° C. / min, the temperature is raised to 1600-1900° C., and the insulation time is 1-3 hours.

10. A 2.5D woven carbon fiber preform reinforced Zr-based composite material prepared according to the method for preparing a 2.5D woven carbon fiber preform reinforced Zr-based composite material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A carbon fiber reinforced carbon-silicon carbide-zirconium carbide composite material and its preparation method

    CN111099911B

Cited By

  • Silicon carbide fiber reinforced ceramic-based composite material as well as preparation method and application thereof

    CN119874377A

  • 2.5 D woven ceramic-based composite material based on C / C composite material and preparation method of 2.5 D woven ceramic-based composite material

    CN120518403A

  • Ceramic-based composite material based on precursor-infiltration agent modification and preparation method

    CN120923250A